Media errors and the 'nutty professor': Riding the journalistic boundaries of the Sandy Hook shootings. (February 2016) - Berkowitz, Dan; Liu, Zhengjia Michelle
This study explores the relationship between social media and threats to journalism's authority during coverage of the mass shootings at Sandy Hook Elementary School. Two related threats are examined. One threat concerned widespread errors in early reporting of the shootings. A second threat came shortly after, in the aftermath of a communication professor's blog claiming a conspiracy between media and government. Through textual analysis of news articles, columns, and blogs, the study considers the concepts of paradigm repair, boundary work, what-a-story news, and memory in the renegotiation of journalistic authority. Findings suggest that with increased reliance on social media for reporting, increased media errors threaten the boundaries of appropriate professional journalistic practice, which both mainstream and social media attempt to rebalance.